SOCIODEMOGRAPHIC CHARACTERISTICS, USE OF DRUGS, DEPRESSION AND PATHOLOGICAL GAMBLING IN A GROUP OF WOMEN FROM PUNTA UMBRÍA (HUELVA-SPAIN): A DESCRIPTIVE STUDY - Arbinaga Ibarzábal, Félix (Anales de Psicología / Annals of Psychology, 2000)
The paper is a presentation of the results obtained in a group of 308 women (8-73 years) about gambling and pathological gambling, measured with the SOGS in the case of the adults and SOGS-RA in the case of those under age. The data indicates that 93,8% of the women would not have gambling problems, 3,6% would have slight ones and 2,6% could be considered pathological gamblers. 54,6% of the women with slight problems and 37,5% of the probable pathological gamblers would suffer from moderate or severe depression. 33,3% of the adult gamblers and 16,7% of those considered pathological would probably be alcoholics. Although it is impossible to establish a profile of the woman gambler from the studies carried out up to now due to the lack of specific information the data does indicate the necessity of deepening our knowledge of the characteristics that gambling shows in women.